Gamma-heteroatom directed stereocontrolled staudinger cycloaddition reaction of vinylketenes and imines - Shaikh, Aarif L.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron Letters, 2006)
Vinylketenes possessing a gamma-heteroatom, on Staudinger cycloaddition reaction with imines gave trans-3-vinyl-beta-lactams in very good yields. The vinyl side chain stereoselectively adopts the Z-configuration in the transition state to stabilize the vinylketene and produces, exclusively, trans-3-vinyl-beta-lactams. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: imines; Staudinger reaction; stereoselective synthesis; vinylketenes